A zooarchaeological analysis of the faunal remains from Ratho Kroonkop, Limpopo Province, South Africa - Croll, Kathryn D. (My University, 2024)
Ratho Kroonkop is one of several hilltop sites in the Shashe-Limpopo Confluence Area (SLCA) that Schoeman (2009; also see Brunton et al. 2013) interpreted as a rain control site. Investigating how people (hunter-gatherers or farmers or both) selected, obtained, butchered and disposed of animal remains at Ratho Kroonkop, provides a window into people’s relationship with animals in this liminal space on the edge of the SLCA, and possibly, more broadly in society as a whole. In this study, I conducted taxonomic and taphonomic analyses on faunal remains from Ratho Kroonkop to elucidate engagement with animals between AD 900 and the 1600s. The identification of distinct temporally specific patterns in the Ratho Kroonkop faunal assemblage rests on a combination of my analyses of the faunal remains and radiocarbon dates. However, the interpretation of patterns in the data was informed by the comparison of the faunal assemblage with that from other sites in the region, and the integration of ethnography on both hunter-gatherers and farmers, and in particular, ethnographic accounts about rain control and beliefs related to animals. It can be challenging for archaeologists to tease apart mundane and ritual use of animals by people in the past, especially when limited ethnography is available. A possible avenue for engaging with these nuances is through exploring patterns within datasets, for example, the differences in faunal processing between the three areas of activity at Ratho Kroonkop; the two rock tanks have taxa that would not ordinarily be consumed and have more evidence for ‘ritual’ use of fauna than the Central Area. Consequently, I suggest that the mid-second millennium faunal assemblage from the Central Area relates to mundane faunal remains processing, whereas the faunal assemblage in the two rock tanks relates to less mundane purposes from the early to mid-second millennium. My study of the faunal remains from Ratho Kroonkop details the quotidian uses of animals at the site and delves into the human-animal relationships expressed at Ratho Kroonkop. Accepting Ratho Kroonkop as a rain-control site, the animals identified and their spatial locations at Ratho Kroonkop indicate that they transcended quotidian use. The animals were vital for rain control and particular animals (specifically Ovis/Capra v and very large mammals) had agency, potency and the power to prevent or withhold rain if treated inappropriately (in the case of hunter-gatherers).
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2023
Keywords: Hilltop sites; Faunal